Model Pemberdayaan Masyarakat Melalui Pengembangan Ekowisata Kelurahan Sumber Rejo Kecamatan Balikpapan Tengah - Prasetya, Candraditya; Harahap, Syanti Dewi (SAFE-Network, 2024)
This Study aims to explain a model of community empowerment through ecotourism development in Sumber Rejo Village, Balikpapan District. Qualitative descriptive methods are used to describe tourism development planning models based on community empowerment and describe ecotourism development strategies. Data analysis was carried out on data from in-depth interviews to determine the community's response regarding the stages of the ecotourism development process through community empowerment. The research results explain that the community is aware of the importance of developing their own capacity to form attitudes, behavior and thought patterns that can foster confidence, enthusiasm and motivation in developing Sumber Rejo Village with its various potentials so that it becomes ecotourism. The community has knowledge and skills in organizational development, as well as building values of togetherness, cooperation, mutual appreciation and respect, mutual help, mutual trust, hard work, a sense of justice and motivation. The research results also explain that the ecotourism development strategy is branding, upgrading, legality, packaging and marketing to maximize the production of processed water spinach and maximize sales results so as to increase opportunities for sustainable development of tourist villages.